Issues to Improve the Quality of Financial Results Audit - Avlokulov Anvar Ziyadullaevich; Eshbekova Zilola Turgunboevna (International Journal on Economics, Finance and Sustainable Development, 2022)
In this article reviewed the main directions of improving the quality of auditing of financial results and control procedures. Also, it is recommended applying quality control procedures in stages of the audit